Flash! Enhanced memorization aid for ADHD/ Julia Hannah Zulkifli, Rafidah Abd Karim and Ramlee Mustapha - Zulkifli, Julia Hannah; Abd Karim, Rafidah; Mustapha, Ramlee (2023)
Flash! is an application that uses a gamified approach to learning for ADHD students who struggle to focus and retain their memory. It capitalizes on the Leitner System of spaced repetition where a student learns and reviews materials in spaced intervals which increases over time. These intervals also consider the Ebbinghaus Forgetting Curve, which hypothesizes the decline of memory retention over time. The curve shows how information is lost over time when there is no attempt to retain it. Flash! includes an automatic function to set up spaced intervals for each flashcard. Thus, ADHD students merely need to open the app and flip through the cards for a few minutes (or even a few seconds!) at any time, place or position. This ensures the student can get their daily memorization sessions at an optimum focus level. In short, with a quick tap of a button, ADHD students are able to ace exams in a Flash! In short, with quick taps of a button, ADHD students are able to ace exams in a Flash!